The relationship between hostility and anger with coronary heart disease in patients - Sadeghi, Bahman (J Educ Health Promot, 2020)
BACKGROUND: Cardiovascular disease accounts for 40% of the world's fatality and after accidents and traumas, is the second leading cause of death in Iran. Given the role of psychological characteristics such as hostility and anger in the development of certain behaviors and habits affecting heart problems, this study aimed to investigate the relationship between hostility and anger with coronary artery disease. METHODOLOGY: In this cross-sectional study, 320 patients referring to the hospital with coronary artery stenosis enrolled in the study and were available for angiography. Data collection tools included demographic and disease status questionnaires and aggression questionnaire. The data were analyzed by SPSS software version 16, and Spearman's correlation coefficient, Student's t-, and one-way analysis of variance tests was used for the statistical analysis. RESULTS: In this case, we have the following. Out of 302 cases, 183 were males and 119 were females. One hundred and ninety-seven patients with coronary artery disease and 105 patients with angiography had no coronary artery disease. CONCLUSION: People with coronary artery disease and healthy controls had no significant differences in demographic characteristics, history of illness, and education. Furthermore, there was no statistically significant relationship between hostility and anger with vasoconstriction. Since there is no relationship between hostility and anger with coronary artery disease, further studies are needed to investigate the presence of mediating variables to design appropriate and preventive interventions.